Peningkatan Pengetahuan Melalui Bimbingan Belajar Terhadap Anak Sd Di Dukuh Sambiroto Desa Sindon - Andromedha Wiratama; Restu Nawaf Bayu Ilham; Yunita Primasanti; Anita Oktaviana Trisna Devi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Education is an effort to guide and develop human knowledge and personality, both mentally and physically. Tutoring has a big influence on children's developmental achievements, this was proven after the author tried to apply several theories and methods to children. The method of this service is lecture and discussion. The result of this service is that tutoring children can improve the knowledge and insight that has been previously taught by the teacher. in Dukuh Sambiroto. The conclusion from the service carried out by the author is that tutoring has proven to be very effective and can increase children's learning knowledge.